1983
DOI: 10.1902/jop.1983.54.7.441
|View full text |Cite
|
Sign up to set email alerts
|

The Incidence of Clinical Infection After Periodontal Surgery: A Retrospective Study

Abstract: A large-scale retrospective study was undertaken to determine the incidence of clinical infection after periodontal surgery and the effectiveness of prophylactic antibiotic therapy in preventing postoperative infection. All second-year postgraduate students reviewed their patient records and completed a questionnaire. Eight infections were found in 884 operations performed without antibiotics, while one infection was found in 43 operations performed with antibiotics. Of 268 operations involving osseous surgery… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
32
0
1

Year Published

1999
1999
2023
2023

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(41 citation statements)
references
References 6 publications
7
32
0
1
Order By: Relevance
“…None of the patients had any noticeable systemic effect following surgery. These results correspond with the reported results of the studies done earlier,[278910] but literature review has supported the potential beneficial effects of prophylactic antibiotics in patients with systemic involvement.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…None of the patients had any noticeable systemic effect following surgery. These results correspond with the reported results of the studies done earlier,[278910] but literature review has supported the potential beneficial effects of prophylactic antibiotics in patients with systemic involvement.…”
Section: Discussionsupporting
confidence: 91%
“…[56] On the other hand, many well-conducted studies have not supported the routine use of antibiotics after periodontal surgery and concluded that antibiotics should be used only when there is a medical indication or when the infection has already set in. [27891011]…”
Section: Introductionmentioning
confidence: 99%
“…Some reports (Kidd & Wade 1974) support the concept that healing is more rapid and the discomfort is smaller under antibiotic (penicillin) coverage during periodontal surgery. However, other studies (Pack & Haber 1983, Checchi et al 1992, Powell et al 2005) do not support the routine use of prophylactic antibiotics, such as tetracyclines (Checchi et al 1992), penicillin or erythromycin (Pack & Haber 1983) and cephalexin (Appleman et al 1982), because these regimens were ineffective in preventing post‐operative infection. They concluded that unless there is a medical indication, there is no justification for using prophylactic antibiotic in periodontal surgery.…”
Section: Resultsmentioning
confidence: 99%
“…One failure involving a crossover design showed no benefit of metronidazole when used following surgery (Mahmood and Dolby, 1987), and since this prophylactic indication is not of value for any antimicrobial agent (Pack and Haber, 1983;Tseng et al, 1993), this outcome was to be expected. The other failure also involved a cross-over design in which both groups received metronidazole separated by a 10-week interval (Sterry et al, 1985).…”
Section: (D) Diagnosis Of An Anaerobic Infectionmentioning
confidence: 99%